Culprit plaque characteristics in younger versus older patients with acute coronary syndromes: An optical coherence tomography study from the FORMIDABLE registry. Issue 1 (12th July 2017) - Barbero, Umberto; Scacciatella, Paolo; Iannaccone, Mario; D'Ascenzo, Fabrizio; Niccoli, Giampaolo; Colombo, Francesco; Ugo, Fabrizio; Colangelo, Salvatore; Mancone, Massimo; Calcagno, Simone; Sardella, Gennaro; Amabile, Nicolas; et al.
Abstract: Objectives: Culprit plaque characteristics in young patients who experience an Acute Coronary Syndrome (ACS) evaluated by OCT (Optical Coherence Tomography) have to be defined. The OCT‐FORMIDABLE is a multicentre retrospective registry enrolling consecutive patients with ACS who performed OCT in 9 European centres. Methods: Patients were divided in two groups according to age at presentation: juvenile‐ACS (age ≤ 50 years) and not juvenile‐ACS (age > 50 years). Primary end‐point was the prevalence of plaque rupture (PR). Secondary end point was the prevalence of thin cap fibro atheroma (TCFA), fibrocalcific and fibrotic plaque. Results: 285 patients were included, 71 (24.9%) in juvenile‐ACS group and 215 (75.1%) in not juvenile‐ACS group. Younger patients showed a trend for a higher prevalence of TCFA (70 vs. 58%, P  = 0.06) and thrombus presence (62 vs. 51%, P  = 0.1), while no statistical difference concerning PR (70 vs. 64%, P  = 0.29). Of interest patients younger that 35 years showed a higher prevalence of PR compared to patients aged between 35 and 45 or 45 and 50 years (100 vs. 72 vs. 55%, P  = 0.03). Culprit plaque in juvenile‐ACS group showed more frequently a reduced mean cap thickness (119 ± 66 vs. 155 ± 95 nm, P  = 0.05) and less frequently fibrotic (32 vs. 57%, P  < 0.001) or fibrocalcific (17 vs. 36%, P  = 0.003) characteristics. Conclusion: young patients with ACS show a trend for a higher prevalence of culprit PR, a thinner cap and less fibrotic or fibrocalcific components.